Efficacy of Sumatriptan/Placebo versus Sumatriptan/Propofol Combination in Acute Migraine; a Randomized Clinical Trial - Farahmand Rad, Reza; Zolfaghari Sadrabad, Akram; Jafari, Mohammadali; Ghilian, Marzieh (Archives of Academic Emergency Medicine, 2022)
Introduction: Migraine headaches can cause severe pain for patients and lead them to multiple visits to the emergency department (ED). This study aimed to evaluate the efficacy of propofol + sumatriptan combination in comparison with sumatriptan alone in the management of acute migraine headaches. Methods: This triple-blind clinical trial involved patients who referred to two emergency departments with acute migraine headaches. Patients were randomly assigned to control (sumatriptan and placebo) or intervention (propofol and sumatriptan) groups for comparison of the efficacy and side effects of treatment. Results: In this study, 60 patients were included whose mean age was 31±8.8 years, and headaches were more common among women. After 30 and 60 minutes from the beginning of treatment, the mean pain score reduction in the intervention group was significantly greater than that in the control group (p=0.012, p=0.024). In addition, the rate of chest tightness in the control group was significantly higher than the intervention group. The absolute risk reduction of adverse events (Chest tightness, Bradycardia, hypotension, and etc.), in patients with acute migraine headache taking propofol and sumatriptan treatment, was 32.18% (95% CI: 8.02 – 56.35). Conclusions: This study supports the use of propofol for treatment of acute migraine headaches and shows that combining sumatriptan with propofol is more effective in relieving migraine headaches and the associated symptoms than using sumatriptan alone. However, more studies with longer follow-ups are still needed.